Behavior of the real exchange rate in the long run: empirical evidence in eight Latin American countries - León Astete, Javier; Oliva, Carlos (Universidad del Pacífico, 1990)
This paper uses a variance ratio statistic in order to capture the importance of the non-stationary component in the real exchange rate in 8 Latin-American countries. The outcome is then used to determine the behavior of this variable in the long run. The authors conclude that the real exchange rate shows a quasi-stationary process in all the countries, with an important mean-reverting component that reverts part of the innovation in a less than five years period.​